Expression profile of bowman-birk protease inhibitor gene from Malaysian rice cultivars (MR211&MR220) under drought stress - Wong, Sim Yee (2015)
Drought adversely influences rice (Oryza sativa L.) growth and production. The understanding of rice plant responses toward drought stress can help to generate more drought-tolerant cultivars to achieve the full self-sufficiency level (SSL) in rice production by 2020 target in Malaysia. Currently rice researches have shown great interest in understanding plant protease inhibitors (PIs) as a way to improve plant resistance to drought. In this study, Malaysian rice cultivars i.e. MR211 and MR220 were treated with artificial drought stress induced by 6% PEG 6000 at 5 different time points. RT-PCR analysis was then performed to investigate the gene expression profile of Bowman-Birk type trypsin protease inhibitor (BBI) in both rice cultivars after treatment. The expression level of each DNA fragment was compared. The gene expression in both cultivars was up-regulated with the increase in drought stress exposure time until a peak level was reached. DNA sequence analysis showed that the isolated gene was about 300bp. Conserved domain with the protein superfamily which belongs to BBI was found in the isolated gene, proving that the BBI gene was identified from both cultivars. Besides, after 1 week of drought stress treatment, proline accumulation in both cultivars was also studied. Proline accumulated in both MR220 and MR211 under drought stress. BBI and proline accumulation help in drought-stress tolerance in MR211&MR220.